Burden of Cataract and Surgical Interventions in South Asia : A Narrative Review (Rupandehi Campus Journal, 2025)
This study explores the prevalence of blindness primarily caused by cataracts in South Asia and evaluates the availability of eye care services. Drawing from books and research articles, it compares eight countries, noting cataracts as the leading cause of blindness (58%) followed by refractive errors and glaucoma. Cataract surgery coverage stands at 71%, yet access remains limited due to lack of awareness, low health-seeking behavior, inadequate infrastructure, and high costs. The study emphasizes the need for regional cooperation, targeted awareness campaigns, and improved healthcare access to reduce the burden of preventable blindness across the region.